A New Small Dual-Band Elliptical Microstrip Antenna for Ku/K Band Satellite Applications - Mohamed Mahfoudh Harane; Hassan Ammor (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
In this paper a new design of a dual small band small elliptical microstrip antenna is proposed for Ku and K band satellite applications. The basic antenna structure is an elliptical patch with inset-feed, which is modified by adding two rectangular slots in the radiation patch. The proposed antenna has been designed and fabricated on 1.58 mm thick FR4 substrate whose dielectric constant is 4.4, with dimensions of about 10×12×1.58 mm³. The antenna structure was validated using two different electromagnetic solvers and by measuring the results using a Vector Network Analyzer (VNA). The measured and simulated results show two resonant frequencies that define two bandwidths. Moreover, the proposed antenna frequency bands and the consistent and symmetrical radiation patterns make it an appropriate candidate for many applications such as the Ku/K band satellite application and wireless communications.